SENSITIVITY ANALYSIS OF HYDROSTATIC PARAMETERS WITH RESPECT TO DISPLACEMENT CHANGES ON THE MINI BORNEO BARGE - Romadhoni, Romadhoni; Santoso, Budhi; Utama, IKAP (Marine & Earth Science and Technology Research Center, DRPM, ITS, 2025)
This study presents a systematic sensitivity analysis of key hydrostatic parameters, keel to buoyancy distance (KB), metacentric radius (BM), and metacentric height (GM), with respect to incremental changes in displacement for the Mini Borneo barge. Utilizing only the vessel’s official stability booklet data, natural cubic splines were fitted to the discrete hydrostatic tables to reconstruct continuous functions for each parameter over the displacement range of 256.6 t to 1641.0 t. First derivative functions were then derived analytically and cross-validated via centered finite difference, enabling high-resolution evaluation of ∂KB/∂Δ, ∂BM/∂Δ, and ∂GM/∂Δ at 0.01 t increments. Results indicate that KB sensitivity peaks at a moderate load of approximately 436.6 t (0.00045 m/t), whereas BM and GM sensitivities reach their maxima at full-load conditions near 1641.0 t (0.00086 m/t and 0.00092 m/t, respectively). Critical displacement intervals were identified around these peaks, highlighting narrow bands where small weight additions most profoundly affect stability. These findings inform the definition of safe-loading envelopes and ballast-management strategies, providing practical thresholds to maintain regulatory stability margins without the need for additional sea trials. The methodology is readily generalizable to other small craft equipped with hydrostatic booklets..